2024
DOI: 10.1016/j.jvoice.2021.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Face Mask on Voice Production During COVID-19 Pandemic: A Systematic Review

Abstract: Summary: Objective . The Coronavirus Disease 2019 (COVID-19) is an ongoing global pandemic and wearing face mask is recommended across the globe to break the transmission chain of infection. The masks available in the market are of different types and materials and tend to alter the voice characteristics of the speaker. This can therefore impair optimal communication and the present study is a systematic review exploring the effect of various masks on voice production parameters. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
4

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 36 publications
(102 reference statements)
2
18
0
4
Order By: Relevance
“… 22 In previous studies of healthy populations or simulation situations, acoustic correlates of vocal quality, including the CPP, maximum phonation time, F0, Jitt, Shim, and HNR, were not statistically different between the masked and unmasked conditions. 6 , 7 , 8 , 11 , 12 , 13 , 15 Although a study showed that Jitt and Shim increased by wearing the mask, CPP remained unchanged by wearing the mask, which is in accordance with the current results. 14 Furthermore, the cutoff scores of the CPP measures were similar to those of a previous Korean study (9.9995 dB for sustained vowel, 7.668 dB for running speech), which was performed during the prepandemic period.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“… 22 In previous studies of healthy populations or simulation situations, acoustic correlates of vocal quality, including the CPP, maximum phonation time, F0, Jitt, Shim, and HNR, were not statistically different between the masked and unmasked conditions. 6 , 7 , 8 , 11 , 12 , 13 , 15 Although a study showed that Jitt and Shim increased by wearing the mask, CPP remained unchanged by wearing the mask, which is in accordance with the current results. 14 Furthermore, the cutoff scores of the CPP measures were similar to those of a previous Korean study (9.9995 dB for sustained vowel, 7.668 dB for running speech), which was performed during the prepandemic period.…”
Section: Discussionsupporting
confidence: 92%
“… 27 They are known to degrade speech perception, discrimination, and intelligibility with environmental noise, inducing substantial increase in self-perception of vocal changes, vocal effort, and communication stress. 8 , 9 , 28 , 29 , 30 , 31 Moreover, they increased perceived vocal symptoms and difficulties in coordinating speech and breathing during speech production, especially for professional voice users. 32 The effect of wearing masks on speech production and voice parameters needs to be investigated in order to interpret the voice outcome measured in different conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The systematic review conducted by Shekaraiah and Suresh suggests that wearing masks results in vocal fatigue, discomfort, and perceived voice problems, which may be due to the attenuation that all types of facemasks introduce in the audible frequency range. In this sense, surgical masks would offer the least attenuation loss and therefore put the least strain on the speaker's voice [119]. We can obtain some details in the study carried out by the University of Illinois, which shows the attenuation the mask produces in the frequency range above 1000 Hz, which coincides with the range of maximum voice emission, being more pronounced at the front [120,121].…”
Section: Individualsmentioning
confidence: 96%
“…Impact on Face: Wearing masks for long hours leads to physiological and psychological stress. The usage of PPE and masks are associated with unpleasant effects such as headache [32], acne [33], and skin breakdown [34], obstructing vision and communication [35]. Wearing face masks has been shown to reduce the accuracy of facial identification in forensic examinations [36].…”
Section: Medical Implications Of Prolonged Wearing Of Face Masksmentioning
confidence: 99%